2020
DOI: 10.4081/aiua.2020.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Penile-scrotal flap vaginoplasty versus inverted penile skin flap expanded with spatulated urethra: A multidisciplinary single-centre analysis

Abstract: This study is aimed to compare outcomes of penile-scrotal flap vaginoplasty to inverted penile skin flap expanded with spatulated urethra as a singlecentre experience. Data regarding vaginoplasty performed between May 2003 and January 2014 were reviewed. Subjects were divided into two groups according to the surgical technique performed: perineal- scrotal flap vaginoplasty (Group A), and inverted penile skin flap expanded with spatulated urethra vaginoplasty (Group B). All patients underwent to psychological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…28 studies showed outcomes of arousal. [31][32][33][34][35][36][39][40][41][42][43][46][47][48][49][50][51][52][53][54][55][56][63][64][65][66][67][68][69] Arousal encompassed "urge" and any measurable physiological changes reported during arousal. 18 studies encompassed arousal within a standardized questionnaire (FSFI, BISF-W, Q-SF).…”
Section: Arousalmentioning
confidence: 99%
See 4 more Smart Citations
“…28 studies showed outcomes of arousal. [31][32][33][34][35][36][39][40][41][42][43][46][47][48][49][50][51][52][53][54][55][56][63][64][65][66][67][68][69] Arousal encompassed "urge" and any measurable physiological changes reported during arousal. 18 studies encompassed arousal within a standardized questionnaire (FSFI, BISF-W, Q-SF).…”
Section: Arousalmentioning
confidence: 99%
“…18 studies encompassed arousal within a standardized questionnaire (FSFI, BISF-W, Q-SF). [31][32][33][34][35][36][39][40][41][46][47][48][49][52][53][54][55][56] Studies reported between 46.9% and 100% of patients able to be aroused postoperatively (median 85.7%). [31][32][33]35,51,64,65,67,68 Kerckhof et al (2019) found that a significantly lower percentage of patients (15.9%) had difficulties with sexual arousal postoperatively when compared with preoperative patients while controlling for hormone treatment.…”
Section: Arousalmentioning
confidence: 99%
See 3 more Smart Citations